Computed tomography features of benign adnexal mass lesions - Khalda, Ezzat; Mandal, Ashok Kumar; Rahman, Hafizur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Adnexal masses originating from gynaecologic and nongynecologic sources may be benign or malignant. The objective of this study was to describe multi-detector computed tomography features of benign adnexal masses for diagnostic accuracy and disease understanding. Methods: Study retrospectively evaluates the multidetector computed tomography features of benign adnexal mass lesions, which were referred for MDCT examination with a primary diagnosis of adnexal masses on clinical or USG. Patients who underwent MDCT and subsequently underwent surgery and proved to benign adnexal mass lesion on histopathological examination were included in this study. Results: Forty five percent benign adnexal mass were in the age group of 36-50 years followed by 32.7% in the age group of 21-35 years. Common presenting symptoms of benign adnexal masses were pain abdomen or pelvic pain (65.5%) followed by mass abdomen (42%) while in one fourth of the patients it was asymptomatic and detected as incidental finding. Pathologic diagnosis of most common benign adnexal mass detected were serous cyst adenoma (54.5%), followed by mature cystic teratoma (18.2%), mucinous cyst adenoma (14.5%) and par ovarian cyst (9.1%). Benign ovarian mass had a characteristic CT appearance of cystic lesion (83.6%), unilocular (65.5%) with regular/well defined and thin wall (83.6%) with occasional septations (21.8%) and papillary projections (14.5%). Ascitis (5.5%) was an uncommon finding of a benign adnexal mass lesion. Computed tomography was most accurate to characterize mature cystic teratoma with a typical cystic lesion having fat deposition and calcifications. Serous cyst adenoma had a CT appearance of thin walled cyst mass with no septations or solid component. Mucinous cyst adenoma ovary had a characteristic multilocular cystic lesion with different fluid attenuation and thin septations. Endometrioma had a variable CT appearance with uni or multilocular cystic lesion and hyperdense lesion with focal calcifications. Conclusions: Multi detector computed tomography may provide accurate and valuable diagnostic information about benign nature of an adnexal mass lesion.